Signs of Similar Stellar Obliquity Distributions for Hot and Warm Jupiters Orbiting Cool Stars - Marvin Morgan; Brendan P. Bowler; Quang H. Tran; Erik Petigura; Vighnesh Nagpal; Sarah Blunt (The Astronomical Journal, 2024)
Transiting giant planets provide a natural opportunity to examine stellar obliquities, which offer clues about the origin and dynamical histories of close-in planets. Hot Jupiters orbiting Sun-like stars show a tendency for obliquity alignment, which suggests that obliquities are rarely excited or that tidal realignment is common. However, the stellar obliquity distribution is less clear for giant planets at wider separations where realignment mechanisms are not expected to operate. In this work, we uniformly derive line-of-sight inclinations for 47 cool stars ( T _eff < 6200 K) harboring transiting hot and warm giant planets by combining rotation periods, stellar radii, and $v\sin i$ measurements. Among the systems that show signs of spin–orbit misalignment in our sample, three are identified as being misaligned here for the first time. Of particular interest are Kepler-1654, one of the longest-period (1047 days; 2.0 au) giant planets in a misaligned system, and Kepler-30, a multiplanet misaligned system. By comparing the reconstructed underlying inclination distributions, we find that the inferred minimum misalignment distributions of hot Jupiters spanning a / R _* = 3–20 (≈0.01–0.1 au) and warm Jupiters spanning a / R _* = 20–400 (≈0.1–1.9 au) are in good agreement. With 90% confidence, at least ${24}_{-10}^{+7} % $ of warm Jupiters and ${14}_{-8}^{+5} % $ of hot Jupiters around cool stars are misaligned by at least 10°. Most stars harboring warm Jupiters are therefore consistent with spin–orbit alignment. The similarity of the hot and warm Jupiter misalignment rates suggests that either the occasional misalignments are primordial and originate in misaligned disks, or the same underlying processes that create misaligned hot Jupiters also lead to misaligned warm Jupiters.